Peningkatan Kualitas Sumber Daya Manusia Pariwisata di Era Pandemi Covid-19 Berdasarkan Kecerdasan Emosional dan Kecerdasan Intelektual - Arga Sutrisna; Suci Putri Lestari (Universitas Batanghari Jambi, 2021)
The purpose of this article is first to find out emotional intelligence, intellectual intelligence, and the quality of tourism human resources in Pangandaran beach tourism objects after the determination of the Covid-19 pandemic, second to find out how high the influence of emotional intelligence and intellectual intelligence simultaneously on the quality of tourism human resources in Pangandaran beach tourism object after the determination of the Covid-19 pandemic, and the third is to know the effect of emotional intelligence and intellectual intelligence partially on the quality of tourism human resources in Pangandaran beach tourism objects after the determination of the Covid-19 pandemic. The method used to achieve the above objectives is an explanatory research method, the use of this method is because researchers do not only describe empirical facts found in the field, but also intend to analyze and explain the influence between variables. Subjects are human resources for tourism in Pangandaran beach with a sampling system. The results of this study, first, emotional intelligence and intellectual intelligence have a significant effect simultaneously on the quality of tourism human resources in Pangandaran Beach tourism objects. Second, emotional intelligence does not have a partially significant effect on the quality of tourism human resources in Pangandaran Beach tourism objects. This is if interpreted in more detail, where emotional intelligence still has an influence on the quality of tourism human resources in Pangandaran Beach tourism objects but is very small at 1.61%. Third, intellectual intelligence has a partially significant influence on the quality of tourism human resources in Pangandaran Beach tourism objects.